1999
DOI: 10.1103/physreve.60.6188
|View full text |Cite
|
Sign up to set email alerts
|

Multistability and symmetry breaking in the two-dimensional flow around a square cylinder

Abstract: We use numerical methods to study two-dimensional flow passing a square cylinder at low Reynolds numbers, and observe period-1 and -3 vortices behind the cylinder at the same Reynolds number Re. When Re increases from a small number to a critical value Re(c) approximately equal to 320, the system could change from bistability, which maintains the spatial symmetry, to tristability, which breaks the spatial symmetry. Our results suggest many interesting problems for further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Flow field past a square cylinder is investigated for moderate Reynolds numbers (Re = 150-500, Sohankar et al 1999). Shiau et al (1999) used 2D numerical simulations to examine square cylinder instabilities for low Re numbers, where they concluded that as Re > 320, the system could change from bi-stability which maintains the spatial symmetry with a periodic lift coefficient, to tri-stability, which breaks the spatial symmetry resulting in a non-periodic lift coefficient with a non-zero mean. Davis and Moore (1982) investigated numerically 2D flow around rectangles for Re numbers from 100 to 2,800 and the resulting Strouhal numbers were comparable to those from windtunnel tests for Re numbers less than 1,000.…”
Section: Introductionmentioning
confidence: 99%
“…Flow field past a square cylinder is investigated for moderate Reynolds numbers (Re = 150-500, Sohankar et al 1999). Shiau et al (1999) used 2D numerical simulations to examine square cylinder instabilities for low Re numbers, where they concluded that as Re > 320, the system could change from bi-stability which maintains the spatial symmetry with a periodic lift coefficient, to tri-stability, which breaks the spatial symmetry resulting in a non-periodic lift coefficient with a non-zero mean. Davis and Moore (1982) investigated numerically 2D flow around rectangles for Re numbers from 100 to 2,800 and the resulting Strouhal numbers were comparable to those from windtunnel tests for Re numbers less than 1,000.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, however, show this to be actually an intermediate wavelength quasi‐periodic mode as opposed to a subharmonic one . Period‐doubling bifurcations have also been reported by Shiau et al although for a higher Reynolds number false(italicRe=294false) and moving channel wall boundary conditions. An aspect common to all Period‐ N ( N being a small non‐zero integer 2) bifurcations reported so far, is that they have only been seen in 2D simulations .…”
Section: Introductionmentioning
confidence: 52%
“…The unfortunate tradeoff to this approach is a significant loss in simulation fidelity. To combat this, some have employed higher-order numerical methods to improve solution accuracy while still lowering the number of computational cells (Peng et al, 2003;Shiau et al, 1999;Sau et al, 2004). This approach has been shown to be effective when compared to low-order schemes primarily due to the cost savings associated with fewer computational cells.…”
Section: Discussionmentioning
confidence: 99%